PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoschus esculantus) PADA PELAKUAN PUPUK DEKAFORM DAN DEFOLIASI - S, Nadira; B, Hatidjah; Nuraeni, Nuraeni (FAPETKAN UNTAD, 2009)
ABSTRACT The experimental study was carried out in Kassi-Kassi Village, Tamalate District, Makassar to study the effect of dekaform fertilizer and defoliation on the growth and production of okra.Â The method of the study employed a Randomized Block Design with six treatments :i) Without dekaform and without defoliation; ii) one dekaform tablet and without defoliation; iii) two dekaform tablets and without defoliation; iv) without dekaform and with defoliation; v) one dekaform tablet and defoliation; vi) two dekaform tablets and defoliation.Â The results showed that the treatment of two tablets and defoliation produced the largest plant height, number of pods per plant and production of young pods per hectare.